CORRELATION OF IMPACTED MANDIBULAR THIRD MOLAR WITH INCIDENCE OF IPSILATERAL ANGLE AND CONDYLAR FRACTURES IN MANDIBULAR TRAUMA - Syed Yasir Ali Abidi (Army Medical College Rawalpindi, 2020)
Objective: This study aims to evaluate association of impacted lower third molars with incidence of ipsilateral mandibular angle and condylar fractures.